2019
DOI: 10.3389/fimmu.2019.00114
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Identification of a Broad IgG Repertoire Differentiating Patients With S. aureus Skin and Soft Tissue Infections From Controls

Abstract: Background: Although the relevance of humoral immunity for protection against S. aureus skin and soft tissue infections (SSTIs) has been suggested by several animal and human studies, the question of which human antibodies may be protective has so far impeded the development of a safe and effective vaccine. Because most adults have developed certain anti-S. aureus antibodies due to S. aureus colonization or infection, we hypothesized that the titers of antibodies to S. aureus in uninfected controls would diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In patients suffering from acute infection caused by S. aureus , Dryla et al ( 30 ) reported increased IgG titers directed against six of 19 staphylococcal antigens ( 30 ). Rigat et al ( 37 ) confirmed the “nearly universal” natural exposure of humans to S. aureus using a panel of 134 antigens, but found only little changes of the antibody levels due to a clinically significant S. aureus infection ( 37 ). All the aforementioned studies were limited in their dynamic range as only one serum dilution was analyzed per sample, rendering them prone to saturation and limit-of-detection effects.…”
Section: Introductionmentioning
confidence: 99%
“…In patients suffering from acute infection caused by S. aureus , Dryla et al ( 30 ) reported increased IgG titers directed against six of 19 staphylococcal antigens ( 30 ). Rigat et al ( 37 ) confirmed the “nearly universal” natural exposure of humans to S. aureus using a panel of 134 antigens, but found only little changes of the antibody levels due to a clinically significant S. aureus infection ( 37 ). All the aforementioned studies were limited in their dynamic range as only one serum dilution was analyzed per sample, rendering them prone to saturation and limit-of-detection effects.…”
Section: Introductionmentioning
confidence: 99%
“…Serologic detection of anti-S. aureus Abs against acute S. aureus infections such as bacteremia and skin infections are being pursued by other investigators (51)(52)(53)(54). A recent study involving 42 children with invasive S. aureus infections demonstrated that anti-LukAB Abs could be a useful diagnostic predictor (55), although leukocidin was not a biomarker for MSKI.…”
Section: Discussionmentioning
confidence: 99%
“…The non-adjuvanted vaccine induced a rapid and potent antibody response towards the vaccine antigens suggesting that the vaccine induced a memory response, which pre-existed prior to vaccination. This phenomenon can be explained by the fact that humans are virtually all exposed to S. aureus and indeed the presence of antibodies against its antigens in healthy subjects has been documented ( 81 ). The effect for AS03 in boosting the S. aureus vaccine immunogenicity appeared not statistically superior as compared to the non-adjuvanted vaccine ( 82 ).…”
Section: Vaccine Development Technologiesmentioning
confidence: 99%
“…Interestingly, vaccine efficacy (as measured through the development of infection-induced skin lesions) was unaffected when mice were pre-exposed intradermally to a low dose of S. aureus prior to vaccination. As mentioned previously, humans are naturally exposed to S. aureus and harbor pre-existing immunity ( 81 ). Pre-exposing mice to S. aureus therefore represents an encouraging degree of humanization to the mouse model.…”
Section: An Update Regarding Ongoing and Recently Concluded Clinical Trials For S Aureus Vaccinesmentioning
confidence: 99%